Safety Stock and Reorder Point System for RF Media Stock Optimization - Afrizal, Nova; Minardi, Joko; Mahendra, Danang (Universitas Negeri Semarang, 2025)
Purpose: This study develops a web-based inventory management system by applying the Safety Stock and Reorder Point (ROP) methods to address inventory issues at RF Media small and medium enterprises (SMEs) in the printing sector. The system aims to improve operational efficiency and reduce the risk of stockouts, which frequently occur in SMEs due to their reliance on manual inventory processes. Methods: This study develops a web-based inventory management system by applying the Safety Stock and Reorder Point (ROP) methods to address inventory issues at RF Media small and medium enterprises (SMEs) in the printing sector. The system aims to improve operational efficiency and reduce the risk of stockouts, which frequently occur in SMEs due to their reliance on manual inventory processes. Result: The simulation showed a 21.38% increase in operational efficiency and a 16.10% reduction in the risk of stockouts. The system ensures complete inventory visibility, facilitates faster decision-making, and minimizes manual errors. Usability testing revealed high user satisfaction regarding interface clarity, ease of use, and quick access to inventory information. Novelty: This study introduces an innovative integration of the Safety Stock and ROP methods into a lightweight, cost-effective web-based system specifically designed for SMEs. Inventory digitization plays a critical role in enhancing competitiveness. This system offers a practical and scalable solution for efficient inventory management in SMEs environments with limited resources.